Increasing thermal stability and catalytic activity of glutamate decarboxylase in E. coli: An in silico study. (October 2016) - Tavakoli, Yasaman; Esmaeili, Abolghasem; Saber, Hossein
Graphical abstract: Highlights: Three dimensional model of E. coli GAD was obtained from protein data bank. Point mutation was performed virtually in the active site of the E. coli GAD. Performing mutation separately at positions 164, 302, 304, 393, 396, 398 and 410 increase binding affinity to substrate. The enzyme is predicted to be more thermo- stable in all 7 mutants based on ΔΔG value. Abstract: Glutamate decarboxylase (GAD) is an enzyme that convertsl -glutamate to gamma amino butyric acid (GABA) that is a widely used drug to treat mental disorders like Alzheimer's disease. In this study for the first time point mutation was performed virtually in the active site of the E. coli GAD in order to increase thermal stability and catalytic activity of the enzyme. Energy minimization and addition of water box were performed using GROMACS 5.4.6 package. PoPMuSiC 2.1 web server was used to predict potential spots for point mutation and Modeller software was used to perform point mutation on three dimensional model. Molegro virtual docker software was used for cavity detection and stimulated docking study. Results indicate that performing mutation separately at positions 164, 302, 304, 393, 396, 398 and 410 increase binding affinity to substrate. The enzyme is predicted to be more thermo- stable in all 7 mutants based on ΔΔG value.